Perpindahan Merek (Brand Swithcing Behavior) Pada Air Minum Dalam Kemasan di Kota Pontianak - Lestari, Mar'ah; Kurniari, Dewi; Fitrianti, Wanti (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2020)
The behavior of the displacement of the brand often happens in causes consumer dissatisfaction of the product, thus giving the brand image of the bad against the company's products. At the time the level of consumer involvement is low, consumers will tend to switch brands, looking for other brands out of the market and this situation puts the consumer in an effort to find other variations. Research objectives Analyze the factors that cause the behavior of the displacement of the brand (Brand Switching Behavior) on the purchase of bottled water in the City of Pontianak, on the 150 respondents were selected purposively. Data analysis using Structural Equation Modeling (SEM). The results showed that on the factor of price and product attributes have a positive influence or significant effect on the behavior of the displacement of the brands of bottled water in the City of Pontianak. A positive effect is shown by the Price because Price is an important part in marketing strategy and is considered a consumer in terms of basic needs such as food and drink. The influence of the highest on the indicator of the price of the product with the indicator of the price of the product cheaper and diversification the price of diverse products, where the products with have the ability to compete in the price is a complete make consumers increasingly choose or consume the product, and the product attribute has significant effect with an indicator label and seal packaging that is attractive and safe, product color crystal clear and clean, and taste better on the tongue.